Modelling and Simulation of Electric Fields in the Vicinity of High Voltage Transmission Line - ADEGBOLA, Romaric; FIFATIN, François Xavier; AGBOKPANZO, Richard Gilles; ACAKPOVI, Amevi; AZA-GNANDJI, Maurel (European Journal of Applied Sciences, 2022)
The purpose of this work is to evaluate the electric fields emission in the vicinity of the overhead high voltage transmission lines, owing to rising concerns from people living close to overhead power lines. One of the reasons for the study is the fact that electromagnetic field emissions caused by the overhead power lines could influence the health of surrounding inhabitants. This paper presents an example of the quasi-static electric field calculation occurring under the high-voltage transmission lines of voltage level 330 kV and 161 kV, taking into consideration, real catenary curve shapes of the conductors. The obtained results were compared with exposure limits specified by safety guidelines and regulations. Furthermore, in order to obtain more accurate calculation of the electric field in the vicinity of overhead transmission lines, an application based on Coulomb equation has been used with a combination of the method of image charges dependence of electric field from the positions of the conductor, the observer and its symmetric image. This complex approach gives in combination with finite element method tool for calculation of the electric field intensity. Gmsh and GetDP open source software packages have been used for the simulation of the electric field created near the transmission lines, located in the Republic of Benin. The results of the study revealed that, there were some areas near the overhead high voltage line where the electric field strength exceeded 5 kV/m and 10 kV/m. A comparison of the study results with exposure limits specified by safety guidelines and regulations shows that there is no critical concern for the people living near the transmission lines. Rather, the exposure level seems dangerous for workers and individuals working closely to the line for a long duration. Consequently, the findings of this paper are useful in specifying appropriate clearance distance and duration to be maintained while working on life line as an amendment to existing standards in electromagnetic protection.